Entangling the social: Comments on Alexander Wendt, Quantum Mind and Social Science. (11th April 2018) - Little, Daniel
Abstract: Alexander Wendt suggests that an emerging field of research on quantum consciousness may have important implications for our understanding of the social world as well. He wants us to consider that the operations of the brain are not "classical" but rather quantum‐mechanical, and that this sheds light on the social worker as well. This article casts doubt on these claims. First, the idea of panpsychism (all physical things possess features of consciousness) is implausible on its face. Second, the findings of "quantum decision theory" are much more limited than Wendt recognizes. Third, the biological quantum effects currently subject to investigation are limited in their application to brains and persons by unavoidable limits of time and space scale on quantum effects. The "brain as quantum computer" or "brain as wave function" theory is very implausible given current knowledge.